Selected Decisions 31st Issue 2006 (Without the Cd's) : Thirty-First Issue. (Selected Decisions, 2007)
This paper describes the appropriate maturity of IMF lending in capital account crises, and of the related issue of the mix between Supplemental Reserve Facility (SRF) and Stand-By Arrangement (SBA) resources. Several of the programs supported by exceptional access have been quite successful in helping the member achieve external viability, resume growth with limited vulnerability, and regain access to private markets, although more slowly than at first expected. In other countries, however, the combination of adjustment and exceptional access in the context of the associated political and external environment was not sufficient to avoid a restructuring of obligations. Directors emphasized in particular the importance of rigorous debt sustainability analyses to support requests for exceptional access. Several Directors saw scope for further strengthening the criteria so as to ensure their strict application. Management will consult with the Board specifically before concluding discussions on a program and before any public statement on a proposed level of access.